Writing “Jantur”: Art-based playwriting from Dadaha folklore using Greimas’s actantial model - Riswandi, Budi; Sumiyadi, Sumiyadi; Sunendar, Dadang (Siliwangi University, 2025)
This study develops an operational playwriting framework by integrating Greimas’s actantial model into an Art-Based Research (ABR) process to transform the Dadaha folklore into a contemporary drama script, “Jantur.” Data were drawn from five oral informants, local archival sources, contextual socio-ecological materials, and an auditable trail of iterative script drafts. The ABR process was organized into a cyclical workflow comprising (1) narrative segmentation and motif indexing, (2) actantial mapping of functional relations and value oppositions, (3) canonical narrative schema alignment (manipulation–competence–performance–sanction), (4) semiotic – to - dramaturgical translation into scene objectives, obstacle systems, and escalation patterns, and (5) reflective revision supported by documented decision logs and expert feedback. Rather than treating narrative semiotics as post hoc interpretation, actantial mapping is positioned as a generative compositional logic that regulates character functions, conflict configuration, and ethical causality during drafting. The resulting script demonstrates how creative writing can operate as analytical inquiry, preserving the folklore’s ecological and ethical meanings while recontextualizing them for contemporary performance and learning contexts. Methodologically, the study contributes a replicable semiotic-to-dramaturgical workflow that makes the analysis-to-composition pathway transparent and reusable for folklore-to-drama adaptation and scriptwriting pedagogy. Keywords: Actantial mapping; Art-Based Research; Folklore-to-drama adaptation; Greimas’s actantial model; Playwriting